EDUKASI SENAM ANTI HIPERTENSI TERHADAP PENINGKATAN MANAJEMEN KESEHATAN KELUARGA DENGAN HIPERTENSI - Lisdahayati, Lisdahayati; Zanzibar, Zanzibar; Saprianto, Saprianto; Martadinata, Umar Hasan; Febriandita, Filia (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Hypertension poses a serious threat to public health as it can lead to various complications. The family is often the smallest unit in society and has a crucial role in maintaining the health of its members. Therefore, it is important to focus attention on family health management, especially in the context of families who have members suffering from hypertension. The purpose of the study was to apply antihypertensive gymnastics to the families of hypertensive clients with ineffective health management problems. This research used descriptive case study method. Data were collected by using the assessment format and then by giving a questionnaire sheet. The subjects in this case study were two families whose family members suffered from hypertension. Data analysis uses a comparison of results between two families. After the application of anti-hypertensive gymnastics, the data results were obtained, namely in the client 1 family, blood pressure improved and the family's inability to care for sick family members increased and in your family 2, family knowledge about caring increased and blood pressure improved. The results of blood pressure checks on subject I were 140/100 mmHg to 120/90 mmHg, while on subject II were 150/100 mmHg to 130/90 mmHg. This study concluded that families were able to overcome the ineffectiveness of family health management by implementing antihypertensive exercises. This research is expected to be utilized and carried out by the community to prevent and treat hypertension with antihypertensive gymnastics.